Investigating the antecedents of service quality in low cost carriers and budget airlines - Wan Jusoh, Wan Jamaliah; Irwan, Nurul Aflah (2015)
The emergence of low cost carrier (LCC) services has changed the fundamentals of the aviation industry. With cheap flights and no frill services, LCC has attracted and made it possible for many passengers to fly. Due to this new innovation, has service quality differs from the full service airlines? Therefore, this study was set out to investigate the antecedents of service quality in LCCs or budget airlines. Data was collected from 221 respondents in Kuala Lumpur and at the Low Cost Carrier Terminal in Sepang, Malaysia. The data was analysed using Partial Least Square Method. The findings showed that service quality for LCC were determined by tangibles, price, inflight crew, inflight services, on ground crew and flight schedule. All these factors explained 50 percent of the variance in service quality with tangible as the most important predictor of service quality, followed by price, in flight crew, in flight services, on ground crew and flight schedule. Therefore, it is important for LCCs to understand that these factors contribute to service quality in their industry and to concentrate on these factors and giving the best service so as to be competitive with the full service airlines.